БИОГЕОХИМИЧЕСКИЕ ОСОБЕННОСТИ ИЗЕНЯ В СЕРОЗЕМАХ (Scientific journal of the Fergana State University, 2023)
The biogeochemical characteristics kochia one geochemical landscape formed in the stage and in the dark gray soils typical of the south of Fergana are considered. The leaves on kochia accumulative typical sierozems longer accumulates iodine, gold, silver, and at the roots of gold, zinc, cadmium, samarium and others found out. These elements are the elements of kochia energetic absorption and biological capture.